Black Sea Tourism and the Orient: Bulgarian Visual Images (1920s–1980s) - Georgeta Nazarska (Zeszyty Cyrylo-Metodiańskie)
The article examines the image, interpretations and transformations of the Orient, spread in the Bulgarian cultural space in the 1920s and in the 1960s–1980s. The study centers on the use of the Orient for branding and advertising of the Bulgarian Black Sea resorts as contact zones for ethno-religious and transnational communication. The main sources, analyzed from a social-historical perspective in comparison with other sources and as visual sources in relevant cultural discourse, are Bulgarian postcards and photographs with Oriental motifs aimed at attracting tourists and activating their ideas about the East. Some examples from Bulgarian feature cinema are discussed as well. Original title in Bulgarian: Черноморски туризъм и Ориент: български визуални образи (20-те – 80-те години на ХХ в.).